Intolerance of uncertainty and emotion regulation: A meta-analytic and systematic review. (April 2023) - Sahib, A.; Chen, J.; Cárdenas, D.; Calear, A.L.
Abstract: Intolerance of uncertainty, a transdiagnostic factor manifested across emotional disorders, has been associated with difficulties in regulating emotions. This meta-analysis addresses the lack of synthesis of this relationship. PsycInfo, PubMed, Scopus, and ProQuest were systematically searched for relevant articles published up to and during November 2022. We combined 161 effect sizes from 91 studies ( N  = 30, 239), separating the analysis into maladaptive and adaptive emotion regulation strategies and their association with intolerance of uncertainty. We found a moderate positive relationship between maladaptive, and a moderate inverse relationship between adaptive emotion regulation and intolerance of uncertainty. Analysing the magnitude of relationships revealed that cognitive avoidance and mindfulness were the maladaptive and adaptive strategies respectively which had the largest effect sizes and thus strongest relationships with intolerance of uncertainty. Combining all strategies, cognitive avoidance remained the largest effect size, while expressive suppression had the smallest effect size and was non-significant in its relationship. Further analyses testing study sample, design, and age as moderators found no significant moderator for the relationships between intolerance of uncertainty and emotion regulation strategies. These findings have implications for future intolerance of uncertainty interventions, with emotion regulation as a potential target of change. Highlights: Positive association between uncertainty and maladaptive emotion regulation. Negative association between uncertainty and adaptive emotion regulation. No moderator was found for the relationship between uncertainty and emotion regulation. Cognitive avoidance was the strategy most strongly related to intolerance of uncertainty. Expressive suppression was the strategy less strongly related to intolerance of uncertainty.